Analysis Effect Regional Sustainability Economic Growth and Open Unemployment Rate on Poverty Severity in the Perspective Islamic Economics - Etika, Citra (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2025)
Poverty is a very complex problem. Poverty in the island of Sumatra from 2018-2022 tends to fluctuate. This study aims to determine and analyse the effect of regional sustainability economic growth and the open unemployment rate on poverty severity in 10 provinces in the island of Sumatra in 2018-2022 partially and simultaneously as well as its review in the perspective of Islamic economics. This research is a descriptive quantitative research. The type of data used is secondary data obtained from the Central Bureau of Statistics with a cross section of 10 provinces on the island of Sumatra and a time series for 5 years. The data analysis used is panel data with a random effect model and the tool used to process the data is Eviews 10. The results of this study partially the regional sustainability economic growth variable has a positive and insignificant effect on the severity of poverty in 10 provinces on the island of Sumatra and open unemployment has a positive and significant effect on the severity of poverty in 10 provinces on the island of Sumatra. Simultaneously, the variables of regional sustainability economic growth and open unemployment rate have a significant effect on the severity of poverty in 10 provinces in Sumatra. The inability to fulfil what is not needed is not poverty. Islamic human resources are where the human being himself has a strong faith willing to try and work hard to meet the needs of life to reduce the severity of poverty.